Mental health research in the pre and postgraduate universities of Lima, Peru period 2016-2021 - Sánchez-Carlessi, Héctor Hugo (2023)
Bibliographic and meta-analytic study whose purpose was to present a diagnosis of the characteristics of the undergraduate and postgraduate theses that have been carried out in the state and private universities of Lima, Peru, related to the mental health research, emphasizing the most frequently studied psychological indicators between 2016 and 2021. The study included a sample of 22 universities, both state and private, located in Metropolitan Lima, including Psychology, Medicine and Graduate Schools. In order to collect the information, an identification matrix of 43 psychological indicators linked to mental health in the theses reviewed, was prepared. The information was collected from the Institutional Repositories of each university where we got fully access to the degree theses, supported and approved by the graduates. Only theses related to the field of Mental Health were registered. The study also includes the methodological analysis of every these on mental health that has been carried out by undergraduate and postgraduate graduates of chosen universities in Lima-Peru. Considering the 6-year period that we have studied, the results show that the most frequent psychological indicators have been: stress, anxiety, depression, burnout, coping strategies, resilience, emotional intelligence and personal well- being. On the other hand, very little has been studied about important issues that concern the population, such as violence, psychopathy, anger, hostility, among others.